The PENGARUH MODEL WBT PADA MATA PELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SD NEGERI 89 PALEMBANG - Sridepi; M. Juliansyah Putra; Endie Riyoko (STKIP Subang, 2023)
Learning Indonesian is acquiring information, skills, creativity and attitudes. The formulation of the research problem is how the Whole Brain Teaching model influences in increasing the learning motivation of class III students at SD Negeri 89 Palembang. The aim of this research is to find out whether there are influences, obstacles and impacts in increasing student learning motivation after implementing the whole brain teaching model in class III of SD Negeri 89 Palembang. The research method used is quantitative. Data collection techniques used were questionnaires, observation, documentation. From the research results, it was concluded that there was an influence of the brain teaching model on the learning motivation of class III students at SD Negeri 89 Palembang for the 2022/2023 academic year. From the research results it can be proven that the calculated T obtained is 18.65 and the T table is at a significant level of 0.05 with a value of 2.472. So T count > T table, so that Ho is rejected and Ha is accepted; 2) The magnitude of the influence of the brain teaching model on the learning motivation of class III students at SD Negeri 89 Palembang in 2023/2024 is 67.8%.